Enacting Refugees: An Ethnography of Asylum Decisions - Magalhães, Bruno Eduardo Portela Borges de (2015)
When a foreigner enters the immigration department in Rio de Janeiro and places an asylum request, a complex legal machinery is put in motion to decide if this claim for protection is warranted or not. The process of status determination begins. The end comes a few months later, when the asylum seeker sits across from a police officer and is informed of whether the claim for refugee status has been accepted or denied. Request and decision are the two poles of this narrative. But how is the difference established between those who deserve and don’t deserve protection? Thematically, the research seeks to enrich our understanding of how refugees and migrant are distinguished during status determination. Conceptually, the study serves as an opportunity to reflect on the shortcomings I see in how the scholarship on migration and borders usually conceives the notion of ‘decision’. Drawing on a series of arguments developed in the field of Science Studies, the thesis puts forward a case for approaching asylum decisions in a way that is less focused on the discretion exercised by decision-makers and more attentive to how contingency and heterogeneity impact the enactment of refugees